2008
DOI: 10.4103/0970-1591.40612
|View full text |Cite
|
Sign up to set email alerts
|

Role of botulinum toxin-A in management of refractory idiopathic detrusor overactive bladder: Single center experience

Abstract: BackgroundOveractive bladder (OAB) is a bothersome condition affecting the quality of life, financial constraint on the individual, and community. Anticholinergic drugs cannot be used for long term due to adverse side effects. Botulinum toxin has recently shown promising and encouraging result in management of OAB.AimAim was to study the safety, efficacy, tolerability, and duration of effect of 200 units of botulinum toxin in refractory idiopathic detrusor overactivity.Materials and MethodsThirty-nine female p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In all cases, the symptoms were mild and patients needed no further investigation or treatment. Impaired vision disappeared after a mean of 5 days (range [3][4][5][6][7][8][9][10][11][12][13][14] and eyelid weakness after a mean of 17 days (range 3-41). There was no statistically significant correlation between impaired vision (p = 0.238) or eyelid weakness (p = 0.359) and the injected dose.…”
Section: Impaired Vision and Eyelid Weaknessmentioning
confidence: 99%
“…In all cases, the symptoms were mild and patients needed no further investigation or treatment. Impaired vision disappeared after a mean of 5 days (range [3][4][5][6][7][8][9][10][11][12][13][14] and eyelid weakness after a mean of 17 days (range 3-41). There was no statistically significant correlation between impaired vision (p = 0.238) or eyelid weakness (p = 0.359) and the injected dose.…”
Section: Impaired Vision and Eyelid Weaknessmentioning
confidence: 99%
“…Those studies that reported urgency found a 70.5% (63%-78%) reduction in urgency episodes, and on average, 62% of the patients had no evidence of urgency after a single injection of BTX-A [12,14,[22][23][24]. The single RCT that reported urgency found that BTX-A decreased urgency episodes from 11.69 to 2.48, compared to placebo, which only showed a decrease from 7.31 to 6.02 [12].…”
Section: Urgencymentioning
confidence: 84%
“…This also was accompanied by a decrease in the Pdet max from 63 cm H 2 O to 31 cm H 2 O. First desire to void occurred on average 69 mL later than before BTX-A injection [12,14,[22][23][24].…”
Section: Urodynamic Parametersmentioning
confidence: 86%
See 1 more Smart Citation
“…Lycopene was shown to significantly improve sperm concentration and motility in two reports that included patients with idiopathic OAT [ 37 , 38 ].…”
Section: Reviewmentioning
confidence: 99%